2014
DOI: 10.1080/19440049.2014.900193
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of targeted pyrrolizidine alkaloids in traditional Chinese medicines and selected herbal teas sourced in Ireland using LC-ESI-MS/MS

Abstract: Publications linking hepatotoxicity to the use of herbal preparations are escalating. Herbal teas, traditional Chinese medicines (TCMs) and dietary supplements have been shown to contain pyrrolizidine alkaloids (PAs). Acute PA toxicosis of the liver can result in sinusoidal-obstruction syndrome, also known as veno-occlusive disease (VOD). This paper describes a sensitive and robust method for the detection of targeted PAs and their N-oxides (PANOs) in herbal products (selected herbal teas and TCMs) sourced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 67 publications
1
21
0
1
Order By: Relevance
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. The results obtained in this survey for (herbal) teas correlate well with the results reported from other recent studies (BfR, 2013;Bodi et al, 2014;Mathon et al, 2014;Griffin et al, 2014;Schulz et al, 2015). The most important results of these recent studies will be briefly discussed below.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. The results obtained in this survey for (herbal) teas correlate well with the results reported from other recent studies (BfR, 2013;Bodi et al, 2014;Mathon et al, 2014;Griffin et al, 2014;Schulz et al, 2015). The most important results of these recent studies will be briefly discussed below.…”
supporting
confidence: 89%
“…Since the start of this project some data on the occurrence of PAs in (herbal) teas and supplements have been published elsewhere (Bodi et al, 2014;Griffin et al, 2014;Mathon et al, 2014;Schulz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these products are not regulated and many, inadvertently or intentionally, contain DHPA-producing plants [10]. Some traditional Chinese medicines and other herbal teas sourced in Ireland have been found to contain DHPAs, even though DHPA-containing plants are not listed as ingredients [11]. Similar problems are likely elsewhere.…”
Section: Toxicity Cytotoxicity and Carcinogenicitymentioning
confidence: 99%
“…In hot water extracts from intact and comminuted leaves the amount of PA N-oxides dominated over that of PA free bases, which is in line with other studies However, in the herbal medicines the PAs were present solely in the free-base form. In line with this, Griffin et al (2014) reported that only 6 samples out of a total of 54 herbal medicines contained PA Noxides (Griffin et al, 2014).…”
Section: Discussionmentioning
confidence: 61%